2002
DOI: 10.1001/archpedi.156.11.1086
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Large National Database for Comparative Evaluation of the Effect of a Bronchiolitis/Viral Pneumonia Clinical Care Guideline on Patient Outcome and Resource Utilization

Abstract: Evidence-based care guidelines can successfully influence utilization and clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 21 publications
1
41
0
1
Order By: Relevance
“…Several studies evaluating the implementation of bronchiolitis CPGs for inpatient management at pediatric centres have found a reduction in the use of beta-agonist therapy, chest x-rays, and viral testing. [10][11][12][13] A recent study comparing children's hospitals with bronchiolitis CPGs to hospitals without CPGs found that the presence of a CPG was not associated with less use of unnecessary medication and investigations. 36 Interestingly, when change in bronchiolitis inpatient management was examined across many of these same pediatric hospitals before and after publication of the AAP bronchiolitis CPG, a significant improvement was seen in the use of chest x-rays, systemic corticosteroids, and bronchodilators over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies evaluating the implementation of bronchiolitis CPGs for inpatient management at pediatric centres have found a reduction in the use of beta-agonist therapy, chest x-rays, and viral testing. [10][11][12][13] A recent study comparing children's hospitals with bronchiolitis CPGs to hospitals without CPGs found that the presence of a CPG was not associated with less use of unnecessary medication and investigations. 36 Interestingly, when change in bronchiolitis inpatient management was examined across many of these same pediatric hospitals before and after publication of the AAP bronchiolitis CPG, a significant improvement was seen in the use of chest x-rays, systemic corticosteroids, and bronchodilators over time.…”
Section: Discussionmentioning
confidence: 99%
“…9 Several pediatric centres have demonstrated a reduction in the use of beta-agonist therapy, chest x-rays, and viral testing with implementation of a bronchiolitis clinical practice guideline (CPG). [10][11][12][13] However, most children with bronchiolitis who present to a hospital are treated and discharged from the emergency department (ED). [6][7][8] Many are also managed outside children's hospitals where physicians may be less comfortable with bronchiolitis and less familiar with recent literature regarding bronchiolitis management.…”
Section: Introductionmentioning
confidence: 99%
“…Only 3 studies used some form of external control. 29,30,34 The lack of control subjects in before-and-after studies raises concerns that the change reported could have been due to secular trends rather than the intervention described. All studies did well on evaluation of whether the before-and-after study population shared similar characteristics.…”
Section: Methodologic Qualitymentioning
confidence: 99%
“…The characteristics of the 14 studies [25][26][27][28][29][30][31][32][33][34][35][36][37][38] in this review are described in Table 1, including our qualitative assessment of the categorical type of intervention (described later in further detail): primarily educational (providing voluntary guidelines, presenting conferences); involving significant process change (implementing standardized order sets); and involving significant process change plus the use of a respiratory score. A respiratory score was loosely defined as any multicomponent numerical representation of respiratory effort.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation